2000
DOI: 10.1152/ajpregu.2000.279.1.r118
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular stimulation leads to distinct hemodynamic patterning

Abstract: Previous studies demonstrated that responses of a particular sympathetic nerve to vestibular stimulation depend on the type of tissue the nerve innervates as well as its anatomic location. In the present study, we sought to determine whether such precise patterning of vestibulosympathetic reflexes could lead to specific hemodynamic alterations in response to vestibular afferent activation. We simultaneously measured changes in systemic blood pressure and blood flow (with the use of Doppler flowmetry) to the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
55
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 23 publications
4
55
2
Order By: Relevance
“…However, hindlimb muscle spindles also receive limited sympathetic nervous system innervation (11,14,16), and thus we cannot exclude the possibility that some central nervous system neurons were infected though these projections. Even so, considering the relatively large number of muscle vasoconstrictor fibers that are present within peripheral nerves (10,20,26,27,32), it seems reasonable to conclude that most of the circuitry that was labeled in these experiments participated in controlling muscle blood flow. Caution must also be used when interpreting the results of the experiment involving the injection of PRV recombinants into the left and right gastrocnemius, because the infection of a neuron by one virus can limit its susceptibility to be infected by a second virus (23).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, hindlimb muscle spindles also receive limited sympathetic nervous system innervation (11,14,16), and thus we cannot exclude the possibility that some central nervous system neurons were infected though these projections. Even so, considering the relatively large number of muscle vasoconstrictor fibers that are present within peripheral nerves (10,20,26,27,32), it seems reasonable to conclude that most of the circuitry that was labeled in these experiments participated in controlling muscle blood flow. Caution must also be used when interpreting the results of the experiment involving the injection of PRV recombinants into the left and right gastrocnemius, because the infection of a neuron by one virus can limit its susceptibility to be infected by a second virus (23).…”
Section: Discussionmentioning
confidence: 95%
“…It is possible that the lateral vestibular nucleus and red nucleus are mainly involved in adjusting sympathetic outflow to muscle, but not other tissues. Vestibular signals participate in regulating hindlimb blood flow (20,22,41), and thus the infected neurons in the lateral vestibular nucleus likely are components of the neural pathway that mediates this response. The red nucleus is not typically considered to participate in autonomic regulation but instead plays a fundamental role in motor control in the rat (13,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments conducted on anesthetized (13,15) and conscious (32) cats demonstrated that the vestibular system influences on different vascular beds are not equivalent. Electrical stimulation of vestibular afferents produces opposite changes in the activity of sympathetic nerve fibers innervating arterioles in skeletal muscle of the upper and lower body (15) and reciprocal changes in forelimb and hindlimb blood flow (13).…”
mentioning
confidence: 99%
“…This study observed that, on denervation of the vestibular nerve, tilted cats were unable to maintain arterial blood pressure (8). Later studies reported that stimulation of the otolith organs increases sympathetic outflow and vascular resistance in the cat (12,32,33).…”
mentioning
confidence: 83%